EFEKTIVITAS PELAYANAN ADMINISTRASI RUMAH SAKIT TERHADAP INDEKS KEPUASAN MASYARAKAT - Lina Alfiyani; Asmirati Yakob; Noor Alis Setiyadi; Didik Mulyono; Subagio Utomo; Winda Fitriana Sari (Akbid Wirabuana, 2023)
This study aims to determine the effect of hospital administration services on the community satisfaction index in hospitals. Several previous studies have shown that the quality of administrative services and health services greatly affects patient satisfaction in hospitals. Therefore, this study focuses on hospital administration services and how it affects the community satisfaction index. The research method used was a survey with questionnaires given to patients in hospitals. The data obtained were then analyzed using regression techniques to determine the effect of administrative service variables on the community satisfaction index. The results showed that hospital administration services had a significant influence on the community satisfaction index in the hospital. This shows that good administrative services can increase patient satisfaction in the hospital. Therefore, hospitals need to pay attention to the quality of their administrative services to increase patient satisfaction and improve the hospital's reputation in the community.Keywords : Effectiveness, Hospital Administration, Community Satisfaction Index